CHURCH AND DIALOGUE: BUILD DIALOGUE BETWEEN RELIGIONS IN A VIRTUAL WORLD - Lase, Yunema; Pasaribu, Ferdinan; Bang, Alelang Deprolius; Vicky Paat (Jurnal Matetes STT Ebenhaezer, 2023)
Indonesian is one of the largest countries in the world. Indonesian people have ethnic, cultural, religious and so on. The church is in the midst of a plurality and plurality reality. One of the tasks of the Church is to be light and salt in the midst of the world. The consequence of the Church being in the midst of plurality has become a reality and a challenge. Inter-religious dialogue is an important method for communion between groups and between religious communities. The use of digital media has become a means of building this dialogue. The purpose of this writing is to provide an overview and reality of inter-religious life, especially the church in building dialogue. This research method uses a qualitative approach and by using literature studies.